SPONTANEOUS ADVERSE DRUG REACTION REPORTS FOR NEONATES AND INFANTS IN THE UK 2001–2010. Issue 1 (14th December 2015) - Hawcutt, Dan; Maqsood, Hannah; Gomberg, Simon; Riordan, Andrew; Turner, Mark
Abstract : Aims: The UK Medicines and Healthcare products Regulatory Agency (MHRA) runs a national spontaneous reporting system (Yellow Card Scheme [YCS]) to collect 'suspected' adverse drug reaction (ADR) data. We aim to describe the Yellow card reports received for patients aged ≤1 year for a 10 year period and assess their utility. Methods: Data on all ADRs reported via the YCS in Infants aged ≤1 years from the years 2001–10 were supplied by the MHRA. Results: In total, 3217 suspected ADRs were reported to the YCS between 2001–10 for infants age ≤1 year (Neonates n=97, vaccinations n=2673, infant [neither neonate nor vaccine] n=477). Overall only 0.88 YC per day were received by the MHRA with a male preponderance (Male 50.3%, Female 45.7%); only 25 (0.8%) YC reports stated a gestational age for the affected infant. The medications most frequently reported as suspected of causing an ADR were Swine Flu Vaccine (neonates n=8), Neisseria meningitides (vaccinations n=693) and oseltamivir (infants n=37). Reports associated with vaccinations followed the expected trends. ADRs highlighted by regulators for neonatal and infant populations are not represented in the YCs received by the regulator. Conclusions: The frequency of YCS reports for those ≤1 year is low, with less than 1 per day overall. Neonates are poorly represented, and recording of gestational age is very limited. The YCS appears to be more effective for spontaneous reporting of vaccination-related ADRs in infants than for other medications. Action is required to improve reporting of suspected ADRs that affect neonates and infants.